Analisis Proses Rekrutmen dan Seleksi pada Dali Coffee Cikampek - Febryani, Anastasya Maurita; Wanta; Dwi Epty Hidayaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research illustrates that recruitment practices that only rely on internal relations without opening recruitment to the public are a phenomenon that occurs at Dali Coffee, an MSME in Karawang, West Java. This research aims to understand the recruitment and selection process carried out by Dali Coffee and identify the obstacles that arise in the process. Qualitative methods with a field research approach were used in this research. Observations were carried out to understand directly the recruitment and selection process in the field, while interviews with employees, especially store managers, provided direct insight into these practices. Apart from that, data was also obtained from internal company documents. The research results show that although Dali Coffee prioritizes internal relations in recruitment, the selection process remains strict to ensure compliance with company standards. The obstacles that arise include the risk of high tolerance for employee errors as well as challenges in maintaining the privacy and security of company information. The implications of this research provide insight into Dali Coffee's unique strategy in human resource management and offer recommendations for improving the effectiveness of employee recruitment and selection for similar companies.